Developing writing pedagogy and tertiary learning advice in a disciplinary programme at a New Zealand university : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in English, Massey University, Albany, New Zealand - McMorrow, Martin (Massey University, 2018)
This thesis provides a summary and interpretation of a three-year action research study conducted by a tertiary learning advisor (TLA) at a New Zealand university (referred to in the study as NZU). The study investigated how a TLA, working as an informal writing consultant to staff and students in a disciplinary programme, could make positive contributions to writing pedagogy and TLA practice. The main sources of data were a reflective journal together with interviews and focus groups with NZU students and staff. Interviews were also held with TLAs in other New Zealand institutions to supplement the limited body of relevant literature. Other data comprised classroom observation, recordings made by lecturers while marking student work and disciplinary and institutional documentation. Data was collected and analysed interpretively and subjectively on a continuous, iterative basis. Significant contributions were made to writing pedagogy in this disciplinary programme. Progress was based on incremental ‘small wins’ through prolonged engagement with staff and students. This resulted in the provision of resources and workshops to support students in writing effectively within their disciplinary and professional context. Some collaborations had a formative influence on disciplinary writing practices themselves, particularly reflective writing. However, changes in writing pedagogy remained limited to courses in which staff had volunteered to participate and initiatives requiring substantial time and effort from them had limited success. The main contributions to TLA practice were a greater involvement in classroom teaching and in the professional development of disciplinary teaching staff. However, two shifts in TLA practice which have been advocated in the literature were not supported in this context. Rather than supporting a shift away from one-to-one consultations with students, the study found that they contributed to TLA expertise and to the teaching and learning practices within the programme. The handing over of responsibility for teaching writing from the TLA to disciplinary teaching staff was also not supported; rather, continued involvement of the TLA in direct teaching was seen as consistent with the plurality of expertise and teaching roles which existed in much of the programme.
Keywords: Academic writing; Study and teaching (Higher); New Zealand; Study skills; Tutors and tutoring; Education, Higher